Goodbye to the promised land. Chronicles of latin american migrants returning to the country of origin - Escobedo Rivera, José (2018)
The present research is carried out under the Empiric paradigm "EMIC" - qualitative research -, which will serve as a methodology of the Social Sciences, to know the reasons that had migrants from Latin America and the Caribbean, who settled in a host country of the developed North, for returning to their country of origin saying "Goodbye" to the promised land through the version given by themselves in their Chronicles of Life. The understanding of these testimonies that migrants offered, as subjects in the construction of social reality, were conceived as reflective acts. We have proposed the following objectives with the purpose of knowing the reasons that led migrants to make this decision of returning to their country of origin, since these stories imply an intentionality that claims the role of the subject in the construction of social reality: a) to know the return of the migrants for desired motives, and b) to know the return of the migrants for motives beyond their control.